Multi-FPGA Partitioning Method Based on Topological Levelization - Nabil Kerkiz; Amr Elchouemi; Don Bouldin (Journal of Electrical and Computer Engineering)
This paper presents a partitioning method based on topological ordering and levelization. The proposed method, termed RPL, performs multi-FPGA partitioning by taking into account six different partitioning constraints. We also compare RPL to two existing algorithms. The first approach is a hierarchical partitioning method based on topological ordering (HP). The second approach is a recursive algorithm based on the Fiduccia and Mattheyses bipartitioning heuristic (RP). Experimental results on seven application benchmarks mapped onto three different hardware architectures demonstrated that the proposed RPL approach achieved fewer partitions in less time when compared to the RP and HP algorithms.